A preliminary three-dimensional structure of angiogenin. - Palmer, K A (1986)
A preliminary three-dimensional structure of angiogenin has been computed, based on its homology to bovine pancreatic ribonuclease A. A standard-geometry structure of ribonuclease was first obtained from its x-ray coordinates. The fit of the backbone of angiogenin to that of ribonuclease was then optimized by taking account of amino acid deletions and by minimizing its conformational energy-plus-a-penalty distance function constraining its backbone to that of ribonuclease. Side-chain and backbone dihedral angles were allowed to vary throughout the cycles of energy minimization. In the last stages of minimization, the penalty distance function was removed. A low-energy structure resembling ribonuclease was obtained.